Relationship Between Viremia and Specific Organ Damage in Ebola Patients: A Cohort Study. (20th August 2017) - Lanini, Simone; Portella, Gina; Vairo, Francesco; Kobinger, Gary P; Pesenti, Antonio; Langer, Martin; Kabia, Soccoh; Brogiato, Giorgio; Amone, Jackson; Castilletti, Concetta; Miccio, Rossella; Capobianchi, Maria Rosaria; et al.
Abstract : The pathogenesis of Ebola virus disease on specific organ dame remains poorly understood. This study provides evidence to support that Ebola virus may have a direct role in the muscular damage and in the imbalance of the coagulation system. Abstract: Background: Pathogenesis of Ebola virus disease remains poorly understood. We used concomitant determination of routine laboratory biomarkers and Ebola viremia to explore the potential role of viral replication in specific organ damage. Methods: We recruited patients with detectable Ebola viremia admitted to the EMERGENCY Organizzazione Non Governativa Organizzazione Non Lucrativa di Utilità Sociale (ONG ONLUS) Ebola Treatment Center in Sierra Leone. Repeated measure of Ebola viremia, alanine aminotransferase (ALT), aspartate aminotransferase (AST), bilirubin, creatine phosphokinase (CPK), lactate dehydrogenase (LDH), activated prothrombin time (aPTT), international normalized ratio (INR), creatinine, and blood urea nitrogen (BUN) were recorded. Patients were followed up from admission until death or discharge. Results: One hundred patients (49 survivors and 51 nonsurvivors) were included in the analysis. Unadjusted analysis to compare survivors and nonsurvivors provided evidence that all biomarkers were significantly above the normal range and that the extent of these abnormalities was generally higher in nonsurvivors than in survivors. Multivariable mixed-effects models provided strong evidence for a biological gradient (suggestive of a direct role in organ damage) between the viremia levels and either ALT, AST, CPK LDH, aPTT, and INR. In contrast, no direct linear association was found between viremia and either creatinine, BUN, or bilirubin. Conclusions: This study provides evidence to support that Ebola virus may have a direct role in muscular damage and imbalance of the coagulation system. We did not find strong evidence suggestive of a direct role of Ebola virus in kidney damage. The role of the virus in liver damage remains unclear, but our evidence suggests that acute severe liver injury is not a typical feature of Ebola virus disease.